2009
DOI: 10.1242/jcs.048090
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear signaling by the APP intracellular domain occurs predominantly through the amyloidogenic processing pathway

Abstract: SummaryNuclear signaling by the APP intracellular domain occurs predominantly through the amyloidogenic processing pathway

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
110
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 79 publications
11
110
0
Order By: Relevance
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms4330 ARTICLE the exact molecular mechanism of how APP-mediated regulation of miR-574-5p transcription is unclear, we speculate that APP may directly bind to the genomic regions surrounding miR-574-5p through intracellular C-terminal Domain (AICD) of APP, given that AICD can translocate to nucleus upon phosphorylation of APP and mediate some nuclear signalling events [26][27][28] . Next, what is the molecular target of miR-574-5p in regulating the proliferation and differentiation of NPCs?…”
Section: Discussionmentioning
confidence: 99%
“…NATURE COMMUNICATIONS | DOI: 10.1038/ncomms4330 ARTICLE the exact molecular mechanism of how APP-mediated regulation of miR-574-5p transcription is unclear, we speculate that APP may directly bind to the genomic regions surrounding miR-574-5p through intracellular C-terminal Domain (AICD) of APP, given that AICD can translocate to nucleus upon phosphorylation of APP and mediate some nuclear signalling events [26][27][28] . Next, what is the molecular target of miR-574-5p in regulating the proliferation and differentiation of NPCs?…”
Section: Discussionmentioning
confidence: 99%
“…Some recent evidence would support this viewpoint (20,46), although direct competition between the ␣-and ␤-secretase pathways has more commonly been assumed. Using a cell-based Gal4-driven luciferase reporter gene assay for ␥-secretase-mediated cleavage of APP, Hoey et al (46) showed that treatment of mouse primary cortical neurons with an ␣-secretase inhibitor (TAPI-1) stimulated luciferase activity, whereas a ␤-secretase inhibitor (C3) substantially decreased luciferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…APP 695 is sequestered along with BACE1 and ␥-secretase complexes into lipid raft domains, and processing of the APP occurs following endocytosis where the acidic interior environment favors the catalytic action of the secretases (46), which are aspartic proteinases. The AICD, in combination with Fe65, is delivered to the nucleus by retrograde transport (20), where it can facilitate specific gene transcription, e.g. of the NEP gene (21,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 70 ␥-secretase substrates, about 30 generate intracellular domains (ICD) with potential activity in transcriptional regulation (33), including AICD, which is mainly produced via the amyloidogenic pathway (34) and not released from plasma membrane-attached APP. The ␣-secretase-derived C-terminal stub C83 did not produce AICD (8).…”
Section: Possible Sources Of Nuclear Aicd A␤ and Taumentioning
confidence: 99%